1985
DOI: 10.1063/1.449243
|View full text |Cite
|
Sign up to set email alerts
|

Rate constants of the reactions of metastable N2(A 3Σ+u) in v=0, 1, 2, and 3 with ground state O2 and O

Abstract: Overall rate constants for the removal of N2(A,v) by O2 and O were measured at 298 K in a rapidly pumped flow reactor using laser-induced fluorescence (LIF) detection of N2(A,v) by excitation in the first positive system of N2, B(3πg)←A(3Σ+u). O atoms were generated in microwave discharges of pure O2 prepared by thermal decomposition of KMnO4. Measured rate constants for N2(A,v)+O2 increased from 2.5×10−12(v=0) to 5.7×10−12 cm3 s−1(v=3). For N2(A,v)+O(3P), they were an order of magnitude larger, rising from 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
116
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(129 citation statements)
references
References 20 publications
13
116
0
Order By: Relevance
“…The coefficients of reactions not already included in SIC 6 are rough estimates based on available measurements (Piper et al, 1981a,b;Slanger and Black, 1981;Thomas and Kaufman, 1985;Thomas et al, 1987;Pavlov and Buonsanto, 1996). These studies list only total quenching rates of N 2 , so the branching into different products must be estimated.…”
Section: A12 Reactions Of Excited Statesmentioning
confidence: 99%
“…The coefficients of reactions not already included in SIC 6 are rough estimates based on available measurements (Piper et al, 1981a,b;Slanger and Black, 1981;Thomas and Kaufman, 1985;Thomas et al, 1987;Pavlov and Buonsanto, 1996). These studies list only total quenching rates of N 2 , so the branching into different products must be estimated.…”
Section: A12 Reactions Of Excited Statesmentioning
confidence: 99%
“…Since the B 3 − u state is mainly predissociated, we have included process (5d) in the channel of the dissociation. Experimental data of Dreyer et al (1974), The calculated total quenching rate coefficients of N 2 (A 3 + u ,v)+O 2 (X 3 − g , v=0) (solid line) are compared with experimental data by Dreyer et al (1974) (crosses), Thomas and Kaufman (1985) Thomas and Kaufman (1985), De Benedictis and Dilecce (1997) are compared with the results of our calculation for vibrational level v=0 in Fig. 7.…”
Section: Processes Of Electronic Energy Transfer and Dissociation In mentioning
confidence: 99%
“…Experimental measurements of the overall rate coefficients for the title reaction have been performed by several groups (Dreyer et al, 1974;Thomas and Kaufman, 1985; De Benedictis and Dilecce, 1997). One of the problems related to the reaction is the estimation of product branching ratios.…”
Section: Processes Of Electronic Energy Transfer and Dissociation In mentioning
confidence: 99%
“…The interaction between N 2 e 3 R u Y j at vibrational levels j 0±7 with O 3 give rise to many reaction channels with the total rate coecients measured by Thomas and Kaufman (1985) (Gattinger et al, 1985, Singh et al, 1996 have suggested that this value is not appropriate for the other vibrational levels, and we use a value of 0.36 recommended by Singh et al (1996).…”
Section: Modelling the Sar Arc Emission At 5577 Nmmentioning
confidence: 99%